2007
DOI: 10.1038/nature05559
|View full text |Cite
|
Sign up to set email alerts
|

C5L2 is critical for the biological activities of the anaphylatoxins C5a and C3a

Abstract: Complement-derived anaphylatoxins regulate immune and inflammatory responses through G-protein-coupled receptor (GPCR)-mediated signalling. C5L2 (also known as GPR77) is a relatively new GPCR thought to be a non-signalling receptor binding to C5a, on the basis of sequence information and experimental evidence. Here we show, using gene targeting, that C5L2 is required to facilitate C5a signalling in neutrophils, macrophages and fibroblasts in vitro. Deficiency of C5L2 results in reduced inflammatory cell infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
249
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(270 citation statements)
references
References 24 publications
17
249
2
2
Order By: Relevance
“…In addition to C5ar, C5l2 represents a second high affinity receptor for C5a and C5a desArg . There is still controversy about the expression of C5l2, its ligands and its functional role in biological responses [4][5][6][7][8]13 . One way in which C5l2 differs from C5ar is in the so-called DRY region of the third intracellular loop (replacement of arginine by leucine), resulting in an uncoupling of C5l2 from G protein interactions 6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to C5ar, C5l2 represents a second high affinity receptor for C5a and C5a desArg . There is still controversy about the expression of C5l2, its ligands and its functional role in biological responses [4][5][6][7][8]13 . One way in which C5l2 differs from C5ar is in the so-called DRY region of the third intracellular loop (replacement of arginine by leucine), resulting in an uncoupling of C5l2 from G protein interactions 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it also remains unclear whether C3a and C3a desarg might exert their anti-inflammatory effects via interaction with C5l2, which has been thought to have anti-inflammatory properties by nonproductively binding C5a [9][10][11][12] . Recent studies suggest that C5l2 can mediate the biological activities of the complement anaphylatoxins C5a and C3a via mitogen-activated protein kinase (MAPK) activation and that C5l2, as a receptor for C3a desArg , contributes to protein acylation and synthesis of triglycerides in adipocytes 7,13 . Like C5ar, C5l2 is abundantly expressed on both myeloid and nonmyeloid cells 14 .…”
mentioning
confidence: 99%
“…C5a is known to have a range of effects on the innate immune cells in particular neutrophils and macrophages: it is a chemoattractant and enhance expression of adhesion molecules on the cells both of which are important to direct the phagocytes from the blood to the site of infection/injury (80,81); the molecule induce phagocytosis and the consecutive oxidative burst to kill the phagocytized microorganisms (64), and it releases enzymes from intracellular granules as well as induces production and release of cytokines (82)(83)(84). The effect of C5aR binding of C5a is most extensively studied while the role of C5L2 is less well understood, although recent studies have indicated both important pro-and anti-inflammatory effects of the C5L2 receptor (85,86). C5aR is also expressed on endothelial cells, where binding of C5a leads to proinflammatory effects like upregulation of the adhesion molecule P-selectin (87), as well as production of cytokines and the important inductor of coagulation, tissue factor (TF) (88,89).…”
Section: Complement and Inflammationmentioning
confidence: 99%
“…Although it does not seem to be G-protein coupled, it has a role in enhancing the downstream effects of C3a and C5a. In neutrophils, macrophages, and fibroblasts, C5L2 modulates downstream mitogenic signaling through ERK 1/2, c-Jun amino-terminal kinase (JNK), MAPK p38, and β-arrestin pathways (34,35).…”
Section: Complement Promotes Oncogenesismentioning
confidence: 99%